2005
DOI: 10.1186/1471-244x-5-33
|View full text |Cite
|
Sign up to set email alerts
|

Public beliefs about causes and risk factors for mental disorders: a comparison of Japan and Australia

Abstract: BackgroundSurveys of the public in a range of Western countries have shown a predominant belief in social stressors as causes of mental disorders. However, there has been little direct cross-cultural comparison. Here we report a comparison of public beliefs about the causes of mental disorders in Japan and Australia.MethodsSurveys of the public were carried out in each country using as similar a methodology as feasible. In both countries, household interviews were carried out concerning beliefs about causes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(100 citation statements)
references
References 23 publications
8
89
1
2
Order By: Relevance
“…This study differs from past research (e.g., Nakane et al, 2005), which examined cross-national differences in MHL between Australians and Japanese. The present study investigated MHL differences between Japanese and American using college students rather than general populations.…”
Section: Introductioncontrasting
confidence: 46%
See 1 more Smart Citation
“…This study differs from past research (e.g., Nakane et al, 2005), which examined cross-national differences in MHL between Australians and Japanese. The present study investigated MHL differences between Japanese and American using college students rather than general populations.…”
Section: Introductioncontrasting
confidence: 46%
“…This tendency may also be associated with the stigma Japanese individuals face when discussing mental illness. Indeed, Nakane et al (2005) concluded that Japanese individuals tended to believe that depression is caused by weakness of character. Furthermore, very few Japanese believe that people can recover from mental disorders, such as depression (Ando, Yamaguchi, Aoki, & Thomickroft, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…physical activity, psychotherapy, hypnosis) as either 'helpful, 'harmful' or 'neither.' Causal beliefs about depression and psychosis were also assessed [19]. Respondents were asked to rate the likelihood of the following as causes for the disorder described in the vignette: 'virus or infection', 'allergies', 'day-to-day problems,' 'the recent death of a close friend or relative,' 'experiencing a recent trauma,' 'childhood problems,' 'genetics,' 'being a nervous person' and 'weakness of character.'…”
Section: Methodsmentioning
confidence: 99%
“…The description of vignettes was designed to fit the diagnostic criteria of DSM-Ⅳ and ICD-10. Respondents were randomly shown male or female versions of the vignettes (Nakane et al, 2005). The target populations of these two surveys were male and female aged 20 to 69.…”
Section: Datamentioning
confidence: 99%
“…This study is a secondary analysis of this data. Their survey comprised common questions about social attitudes for case vignettes: chronic schizophrenia, early-episode schizophrenia, depression, and depression with suicidal thoughts (Nakane et al, 2005). The description of vignettes was designed to fit the diagnostic criteria of DSM-Ⅳ and ICD-10.…”
Section: Datamentioning
confidence: 99%